Choanoflagellates (acanthoecidae, choanoflagellida) from the Weddell Sea, Antarctica, Taxonomy and community structure with particular emphasis on the ice biota; with preliminary remarks on choanoflagellates from Arctic sea ice (Northeast Water Polynya, Greenland) - Thomsen, H. A.; Garrison, D. L.; Kosman, C. (Archiv für Protistenkunde, 1997)
Ice biota studies in the Antarctic region, Weddell Sea, have focused on an examination of single cells and an analysis of community structure of the flagellate assemblage from sea ice and comparisons with planktonic assemblages. Based on extensive light microscopical analysis of 40 samples ranging from open water to “brown-ice” habitats, it became evident through clustering of the data, that the mature choanoflagellate community from ice is significantly different from both the water column community and those encountered in samples derived from newly formed ice (i.e. grease ice, platelet ice, nilas and thin pancakes). The choanoflagellates from sea ice encompasses a range of previously undescribed loricate taxa (Acanthocorbis nana sp. nov., A. weddellensis sp. nov., A. prolongata sp. nov., Apheloecion antarctica sp. nov., A. glacialis sp. nov., A. conicoides sp. nov., Calliacantha frigida sp. nov., C. ankyra sp. nov., Diaphanoeca multiannulata subsp. nov. glacialis, Parvicorbicula corynocostata sp. nov., P. pachycostata sp. nov.). These taxa have been investigated using a combination of light, and electron microscopy. A preliminary investigation of samples from the Arctic (NE Greenland) indicates that the loricate choanoflagellate diversity is significantly lower in Arctic sea ice.